Design and Implementation of a Loss Optimization Control for Electric Vehicle In-Wheel Permanent-Magnet Synchronous Motor Direct Drive System. (May 2017) - Guo, Qingbo; Zhang, ChengMing; Li, Liyi; Zhang, Jiangpeng; Wang, Mingyi
Abstract: As a main driving force of electric vehicles (EVs), the loss of in-wheel permanent-magnet synchronous motor (PMSM) direct drive system can seriously affect the energy consumption of EVs. This paper proposes a loss optimization control strategy for EV in-wheel PMSM direct drive system which can optimize both the loss of PMSM and loss of inverter. The proposed method adjusts the copper loss and iron loss by optimal flux-weakening current, and as a result the PMSM achieve the lower loss in the whole operation range. According to the speed, the PWM frequency is optimized by the proposed control strategy, which can acquire high efficiency of inverter and not affect the stability of the PMSM system in the each operation condition. The optimum flux-weakening current and PWM frequency can be quickly found, and optimal effects of energy loss are verified by theoretical analysis and experimental results.